Influence of processing conditions on the thermal decomposition of SrTiO3 precursors - Silva, Marcia R. S.; Soledade, L. E. B.; Lima, S. J. G.; Longo, Elson [UNESP]; Souza, A. G.; Santos, Ieda M. G. (Springer, 2007)
The present work investigates the influence of milling and calcination atmosphere on the thermal decomposition of SrTiO3 powder precursors. Both pure and neodymium-modified SrTiO3 samples were studied. Milling did not significantly influence numerical mass loss value, but reduced the number of decomposition steps, modifying the profiles of the TG and DTA curves. on the other hand, milling increases the amount of energy liberated by the system upon combustion of organic matter. It was also observed that the milling process, associated to the calcination in an oxygen atmosphere, considerably decreases the amount of organic matter and increases the final mass loss temperature.
Keywords: atmosphere; milling; Pechini method; SrTiO3; thermal decomposition